APLIKASI MINYAK CENGKEH SEBAGAI OBAT BIUS PADA KAKAP PUTIH (Lates calcarifer Bloch) - Bambang Hanggono (Jurnal Perikanan Universitas Gadjah Mada, 2006)
The objective of this study was to determine the safety and efficacy of clove oil as an anesthetic in sea bass (Lates calcarifer) and the potential application of clove oil as anesthetic to facilitate the sea bass fry transportation. Acute toxicity test indicated the 24-hr LC50 value of clove oil in sea bass fry as 30 ppm with slope function of 1.079 (1.05 to 1.107). In efficacy test, fish were exposed to 5, 10, 15, 20 and 25 ppm of clove oil for 15 minutes. At 5 ppm, clove oil caused only sedation effect (partial loss of reaction to external stimuli) while at 20 ppm, fish entered anesthesia stage (failure to respond to external stimuli) within about 3 minutes. Fish recovered from a 15-min period of exposure in 20 ppm clove oil within less than 10 minutes following removal from the anesthetic solution. There was neither mortality nor abnormal behavior of fish during 15-min exposure of clove oil as well as during 7 days post recovery from anesthesia. The potential application of clove oil as an aid in the transport of sea bass fry in plastic bag was also investigated. At 5 ppm, clove oil could reduce activities of the fish without loss of equilibrium (sedation stage) during the 4 hour simulated transport at 50 fish per 1,000 ml sea water (15 ppt). At 20 ppm, clove oil caused loss of equilibrium in fish resulting in the anesthesia stage throughout the 4 hour period. However, there was no improvement on survival rate and fish behavior with the use of clove oil during and after this 4 hour transport. Simulated transport at 50 fish per 500 ml sea water (15 ppt) for 8 hour did show better significant survival rate with additional of 5 and 20 ppm clove oil. In both short and long term transport study, clove oil did show the benefit by reducing the fish activities judging from the reduction of oxygen consumption, ammonia and carbon dioxide levels. Addition of appropriate concentration of clove oil in transport water ensured that the fish would stay calm by reducing fish activity and therefore, prevented any drastic changes of water qualities.